Systematic increase of electrocatalytic turnover at nanoporous platinum surfaces prepared by atomic layer deposition1. Issue 16 (28th April 2015) - Assaud, Loïc; Schumacher, Johannes; Tafel, Alexander; Bochmann, Sebastian; Christiansen, Silke; Bachmann, Julien
<x xml:space="preserve">Abstract</x> An atomic layer deposition reaction for metallic platinum is investigated mechanistically and exploited to generate electrochemically active nanoporous surfaces.